A Phase 3 Randomized Clinical Trial of Chemotherapy With or Without Algenpantucel-L (HyperAcute-Pancreas) Immunotherapy in Subjects With Borderline Resectable or Locally Advanced Unresectable Pancreatic Cancer - Hewitt, Daniel Brock; Nissen, Nicholas; Hatoum, Hassan; Musher, Benjamin; Seng, John; Coveler, Andrew L; Al-Rajabi, Raed; Yeo, Charles J; Leiby, Benjamin; Banks, Joshua; Balducci, Lodovico; Vaccaro, Gina; et al. (Annals of surgery, 2022)
To compare the efficacy and safety of algenpantucel-L [HyperAcute-Pancreas algenpantucel-L (HAPa); IND# 12311] immunotherapy combined with standard of care (SOC) chemotherapy and chemoradiation to SOC chemotherapy and chemoradiation therapy alone in patients with borderline resectable or locally advanced pancreatic ductal adenocarcinoma (PDAC). To date, immunotherapy has not been shown to benefit patients with borderline resectable or locally advanced unresectable PDAC. HAPa is a cancer vaccine consisting of allogeneic pancreatic cancer cells engineered to express the murine α(1,3)GT gene. A multicenter, phase 3, open label, randomized (1:1) trial of patients with borderline resectable or locally advanced unresectable PDAC. Patients received neoadjuvant SOC chemotherapy (FOLFIRINOX or gemcitabine/nab-paclitaxel) followed by chemoradiation (standard group) or the same standard neoadjuvant regimen combined with HAPa immunotherapy (experimental group). The primary outcome was overall survival. Between May 2013 and December 2015, 303 patients were randomized from 32 sites. Median (interquartile range) overall survival was 14.9 (12.2-17.8) months in the standard group (N = 158) and 14.3 (12.6-16.3) months in the experimental group (N = 145) [hazard ratio (HR) 1.02, 95% confidence intervals 0.66-1.58; P = 0.98]. Median progression-free survival was 13.4 months in the standard group and 12.4 months in the experimental group (HR 1.33, 95% confidence intervals 0.72-1.78; P = 0.59). Grade 3 or higher adverse events occurred in 105 of 140 patients (75%) in the standard group and in 115 of 142 patients (81%) in the experimental group (P > 0.05). Algenpantucel-L immunotherapy did not improve survival in patients with borderline resectable or locally advanced unresectable PDAC receiving SOC neoadjuvant chemotherapy and chemoradiation. ClinicalTrials.gov Identifier: NCT01836432.